Types of Politeness Maxim and its Scale Found in Emma 2020 Movie - Suryani, Ni Kadek; Suastini, Ni Wayan (Humanis; Vol 27 No 1 (2023), 2023)
Politeness is the primary notion in this study. The objective was to find the types of politeness maxim and its scale applied by the character in Emma 2020 movie. The analysis was conducted based on the theories proposed by Leech (1983) who formulated the six types of politeness maxim. Leech (1983:123) also proposed the three scales of politeness and two scales based on the theory by Brown and Gilman (1960). The data were taken from the British romance movie entitled Emma 2020. The qualitative method was used for analyzing the data. The analysis found six types of politeness maxim and five types of politeness scale applied by the movie characters with the types of 13 approbation maxim and 24 cost-benefit scales was extremely appear. In addition, there are two types of politeness maxim compete by the same character found in this analysis, and the goals of conversation affected the politeness maxim application.